2011
DOI: 10.1088/0264-9381/28/13/134009
|View full text |Cite
|
Sign up to set email alerts
|

A blind hierarchical coherent search for gravitational-wave signals from coalescing compact binaries in a network of interferometric detectors

Abstract: We describe a hierarchical data analysis pipeline for coherently searching for gravitational-wave signals from non-spinning compact binary coalescences (CBCs) in the data of multiple earth-based detectors. This search assumes no prior information on the sky position of the source or the time of occurrence of its transient signals and, hence, is termed 'blind'. The pipeline computes the coherent network search statistic that is optimal in stationary, Gaussian noise. More importantly, it allows for the computati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 30 publications
0
52
0
Order By: Relevance
“…To compute the SNR, we consider detection via optimal matched filtering (Jaranowski & Królak, 2012), which is based on the cross correlation between the gravity data and a template of the expected gravity strain perturbation. Template-matching techniques have been widely used in modern seismology to detect earthquakes with low SNRs (Frank et al, 2014;Gibbons & Ringdal, 2006;Shelly et al, 2007) and in astrophysics to detect coalescing compact binaries (Bose et al, 2011;Pai et al, 2001).…”
Section: Optimal Matched-filter Detection and Snrmentioning
confidence: 99%
“…To compute the SNR, we consider detection via optimal matched filtering (Jaranowski & Królak, 2012), which is based on the cross correlation between the gravity data and a template of the expected gravity strain perturbation. Template-matching techniques have been widely used in modern seismology to detect earthquakes with low SNRs (Frank et al, 2014;Gibbons & Ringdal, 2006;Shelly et al, 2007) and in astrophysics to detect coalescing compact binaries (Bose et al, 2011;Pai et al, 2001).…”
Section: Optimal Matched-filter Detection and Snrmentioning
confidence: 99%
“…For fixed {τ 0 , τ 1.5 , α, δ}, the maximization over t c , can be carried out very efficiently using the Fast Fourier Transform (FFT) since p|q(t − t c ) is a correlation operation [16]. We call (34) with Θ = {τ 0 , τ 1.5 , α, δ}, the coherent fitness function.…”
Section: Fully-coherent All-sky Searchmentioning
confidence: 99%
“…Events from different detectors are deemed to be in coincidence if their ellipsoids have a nonzero overlap. The coincidence and the coherent strategies of multidetector detection of gravitational-wave signals from inspiralling compact binaries have been compared in [96, 97, 32]. [96] considered detectors in pairs located in the same site and [97] pairs of detectors at geographically separated sites.…”
Section: Network Of Detectorsmentioning
confidence: 99%
“…[96] considered detectors in pairs located in the same site and [97] pairs of detectors at geographically separated sites. The case of three detectors (like the network of two LIGO detectors and the Virgo detector) has been considered in detail in [32], where it was demonstrated that the hierarchical coherent pipeline on Gaussian data has a better performance than the pipeline with just the coincident stage.…”
Section: Network Of Detectorsmentioning
confidence: 99%